If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -29 = -25 + r Solving -29 = -25 + r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-1r' to each side of the equation. -29 + -1r = -25 + r + -1r Combine like terms: r + -1r = 0 -29 + -1r = -25 + 0 -29 + -1r = -25 Add '29' to each side of the equation. -29 + 29 + -1r = -25 + 29 Combine like terms: -29 + 29 = 0 0 + -1r = -25 + 29 -1r = -25 + 29 Combine like terms: -25 + 29 = 4 -1r = 4 Divide each side by '-1'. r = -4 Simplifying r = -4
| 0=1600-60x | | -9=m-(-5) | | -9/12-(-7/4) | | 7y-3x= | | 15x+(-4x)= | | 1/7*1/6 | | 2xy/5y | | -480=20x | | 4-p=5p+16 | | 522=29x | | 4x+5-2x=-19 | | 3[4x-(2x-7)]= | | a/1/a2= | | 1=v-(-12) | | 5x+12=3x-23 | | 8/9*(-1/8)= | | -3+a=26 | | -5(1+5n)=120 | | (5x+2)(5x-1)=0 | | 3x+y-4x= | | 2(2x-7)+3x=21 | | 3p-6=6 | | -2=n-16 | | 8x+2x-4=126 | | (5x+5)-(2+4x)=5 | | y=3x^2-14x+12 | | 4x+2y+y-9x=25 | | (8x^2-2x-38)+(6x^2+4)=0 | | (-5)2-4(5-3)2= | | 6x^2*4x=0 | | 2x(x-2)=5x^2-5x | | 6x^5=-1296x^2 |